Anthropometric variables of futsal referees of Guarapuava/Variaveis antropometricas de arbitros de futsal de Guarapuava - Hortmann, Karin; Ma (Revista Brasileira de Futsal e Futebol, 2013)
The aim of this study was to investigate the anthropometric variables of futsal referees Guarapuava-PR. The sample was composed of 13 referees with mean age of 37.31 ([+ or -] 10.2 years). Subjects underwent the evaluations of body composition were measured where weight, height, skinfold thickness and waist circumference measurements and hip. From these evaluations were described Mass Index (BMI), waist / hip ratio (WHR),% Body Fat (% BF). The results showed average of 26.36 ([+ or -] 3.64 kg/m2), WHR with an average of 0.87 ([+ or -] 0.08), GC 26.65% ([+ or -] 6.72%). The variables investigated in this study showed a higher fat accumulation in body tissues of individuals in this study. Key words: Anthropometry, Body composition, Referee, Futsal. O objetivo do presente estudo foi investigar variaveis antropometricas de arbitros de futsal de Guarapuava-PR. A amostra deste estudo foi composta por 13 arbitros com idade media de 37,31 ([+ or -] 10,2 anos). Os individuos foram submetidos as avaliacoes da composicao corporal onde foram mensuradas massa corporal, estatura, espessura de dobras cutaneas e medidas de circunferencia da cintura e quadril. A partir dessas avaliacoes foram descritos o Indice de Massa Corporal (IMC), Relacao Cintura/Quadril (RCQ), % de Gordura Corporal (%GC). Os resultados encontrados apresentaram media de 26,36 ([+ or -] 3,64 kg/m2), RCQ com media de 0,87 ([+ or -] 0,08), %GC de 26,65 ([+ or -] 6,72%). As variaveis investigadas nesse estudo apontaram um acumulo de gordura elevado nos tecidos corporais dos individuos que compoem esse estudo. Palavras-chave: Antropometria, Composicao corporal, Arbitros, Futsal.